Association Between Perceived Medical Errors and Suicidal Ideation Among Chinese Medical Staff: The Mediating Effect of Depressive Symptoms - Wei, Zhen; Wang, Yifan; Yang, Shijun; Sun, Long (Frontiers in Medicine, 2022)
Both medical errors and suicidal behaviors are important problems for medical staff. Although the association between them was implied in previous studies, their association was not built until now. In this study, the first aim was to build the association between perceived medical errors and suicidal ideation, and we also want to explore the mediating role of depression on the association between perceived medical errors and suicidal ideation among Chinese medical staff. In this study, we interviewed 3338 medical staff in Chinese general hospitals. Questions about Suicidal ideation (SI) and perceived medical errors were interviewed for medical staff. Depressive symptoms were evaluated by the Chinese version of Center for Epidemiologic Studies Depression Scale (CES-D). Social-demographic and occupation-related variables were also assessed in the data collection. This study found that the prevalence of suicidal ideation among medical staff was 9.0%. After adjusted for controlling variables, suicidal ideation was significantly associated with higher level of depression (OR=1.10, p<0.001) and perceived medical errors (OR=2.41, p<0.001). The other associated factors were female (OR=2.21, p<0.001), religious belief (OR= 2.66, p<0.001), and weekly work hours (OR=1.02 p<0.001). The mediating effect of depressive symptoms on the association between perceived medical errors and suicidal ideation was also supported in this study, and it can explain 38.73% of the total effect of perceived medical errors on suicidal ideation. Medical staff perceived medical errors were in higher risk of suicidal ideation, and depressive symptoms can partially mediate the association between perceived medical errors and suicidal ideation. For medical staff experiencing medical errors, some scanning on their suicidal ideation and depressive symptoms are necessary to promote their mental health.